Optimizing School Resource Management to Improve Educational Output at SDN 1 Godong - Zumrotun Zumrotun; Ngurah Ayu Nyoman Murniati; Supandi Supandi (Journal of Educational Sciences, 2026)
The decline in character and learning quality scores on the Education Report Card poses a serious challenge for SDN 1 Godong, a pilot school. This study aims to analyze the optimization of effective, transparent, and accountable resource management (human, financial, and physical) as a strategic solution. Using a descriptive qualitative method with a case study design, data were collected through in-depth interviews, observations, and document reviews. Findings indicate governance anomalies; the availability of physical facilities and financial administrative compliance are not yet linear with instructional quality due to low investment in teacher pedagogical competence (below 10% of the budget). The study's conclusions confirm that optimization requires a radical budget refocusing from physical maintenance to strengthening classroom interactions. Strategic recommendations include debureaucratizing teacher workloads and revitalizing facility functions to reverse the negative trend in education quality.